Continuidades na mudança: um olhar arqueológico sobre os caminhos das Minas Gerais, séculos XVIII e XIX - Anaeli Queren Xavier Almeida (2012)
Two roads built in Minas Gerais the first on the 18th century, Caminho Novo (New Path), and the second on the 19th century, Estrada do Paraibuna (Paraibuna Road) are understood here as part of a strategy used by different forms of government (respectively, Colonial and Imperial governments) to fabricate their power through the establishment of roads, including aspects, such as: the paths drawing, their structures, their relations to inns, and the cities that surrounded them. Analyzing the material culture, and using interpretive archaeology as a theoretical perspective, we understand the roads as forms of domesticating the environment and, therefore, the people who used them. The territorys domestication and control created landscapes, and their study allowed for reconstituting strategies of power reproduction. While in the 18th century roads were seen as facilitators for smuggling goods, in the 19th century they had become fundamental elements for integrating provinces and increasing the Empires wealth.